Multi-criteria analysis to delimit an arid region in central Mexico - Rosas Ávila, Joel; García Romero, Arturo; López García, José; Manzo Delgado, Lilia de Lourdes (Acta Universitaria, 2015)
A multi-criteria analysis applies to the delimitation of a region of hydrological, biological, and cultural wide interest in central Mexico, known as the Mezquital Valley, where the lack of a delimitation of integral character has favored ambiguities in its conceptualization. Multi-criteria analysis consisted on a weighted overlay of structural, bioclimatic, geomorphometric, and historic factors. This analysis showed that the Mezquital Valley is distinguished by geological reliefs composed of volcaniclastic rocks, a linear curvature, temperature and precipitation conditions that indicate an arid environmental favorable for the establishment of Prosopis laevigata (Humb. & Bonpl. ex Willd.) M.C.Johnst, feozem and vertisol soil types subject to irrigation, and 55% of the localities of the hñahñu ethnic group. The study allowed recognize the intrinsic aspects considered important for promoting the identity of the region, favoring the geographic indication, and an appropriate management of the natural resources in the Mesquital Valley.
Keywords: Array; Array; Array; Array; Array